Modifikasi Cadangan Premi Prospektif pada Asuransi Jiwa Seumur Hidup Joint Life Menggunakan Metode New Jersey - Zulfadri Zulfadri; Arnellis Arnellis; Muhammad Subhan (Journal of Mathematics UNP, 2019)
Abstract – Basically the insurance company requires a reserve fund to pay compensation in the event of a claim. Not a few life insurance companies that incur losses beacuse can’t to pay compensation to participants of the insurance. These circumstances can be anticipated if the insurance company has the reserves that have been prepared and it accounted appropriately. One of the methods used to calculate the premium reserve is New Jersey. These method is derived from the formula of prospective reserves. The calculation of the value of reserves method using New Jersey begins by determining the cash value annuity, then calculate the net single premium, and annual net premium , proceed with the counting of net premium advanced and reserves end of the year-t. These method stated that value a reserve premium in the first year is zero, so that insurance companies can use the premium for the need insurance.Keywords – Premium Reserves, New Jersey Method, Prospective, Life Insurance, Joint Life